Architecture x secrets: A study of contemporary secret rooms in Architecture - Johanna, Asplund (My University, 2021)
We are fascinated by the pyramids of ancient Egypt and the many chambers and secrets they keep. Something intrigues us about secret passages and rooms to be yet discovered, unlocked, where you can’t imagine what is hiding behind the next corner. What about the contemporary secret room? This thesis will be touching on intimacy and bodies connected to space, and the importance of having access to A Room of One’s Own (Virginia Wolf, 1928). The manifestation, importance and uses of secret rooms in a contemporary context will be investigated and their relation to power. The application in a contemporary context means that I will place the secret room in a socio-political setting; a center for childbirth located in the city of Gothenburg. The aim is to investigate if secret rooms can be used to re-program space and shift power. I have used: “The master’s tools will never dismantle the master’s house” (Audre Lorde). My interpretation of that quote is that real change can never be achieved within existing power structures. Therefore, I decided to disconnect the birth room from the hospital, placing it in a totally new context; from hidden, to central and public. Through model studies, interpretation of relevant architectural references and the layering of analogue and digital tools a language of the secret room was created. A collection of stories deriving from the voices of a selected target group were translated into architecture trough design iteration and collages. A P(a)lace for Birth is a speculative oasis introducing an alternative narrative far away from white and sterile hospital environments. The aim is to create a conversation piece that question existing power structures and who gets authority and access to certain spaces. I want to expand zonation from private and public by adding secrets, gradients and intimacy. The pressing urgency of this topic is highlighted by the use of exaggeration and a loud design aesthetic. I invite the reader on a speculative journey where the main concept of the new narrative is shifting power structures from institutionalized patient to empowerment and owning your own story.
Keywords: secret rooms, intimacy, power, A Room of One’s Own, unsterile, empowerment